Acute infectious myelopathies - Isada, Carlos M; Miller, Ryan (Current opinion in infectious diseases, 2020)
The patient who presents with an acute spinal cord syndrome with weakness/paralysis of the limbs presents a diagnostic. Two important syndromes are acute transverse myelitis (ATM) and acute flaccid paralysis (AFP). Both can be caused by a number of infectious and noninfectious causes. Since 2014 there have been outbreaks of acute flaccid myelitis (a subgroup of AFP) in the United States, with a national surveillance program underway. In addition, there have been increasing reports of ATM from new and emerging pathogens, and opportunistic infections in immunocompromised hosts. Infectious causes of ATM or AFP need to be ruled out first. There may be important clues to an infectious cause from epidemiologic risk factors, immune status, international travel, MRI, and laboratory findings. We summarize key features for the more common pathogens in this review. Advances in laboratory testing have improved the diagnostic yield from cerebrospinal fluid, including real-time polymerase chain reaction, metagenomic next-generation sequencing, and advanced antibody detection techniques. These tests still have limitations and require clinical correlation. We present a syndromic approach to infectious myelopathies, focusing on clinical patterns that help narrow the diagnostic possibilities.